Comparative Genomics Reveals Potential Mechanisms of Plant Beneficial Effects of a Novel Bamboo-Endophytic Bacterial Isolate Paraburkholderia sacchari Suichang626 - Wang, Kai; Wu, Ying; Ye, Mengyuan; Yang, Yifan; Asiegbu, Fred O.; Overmyer, Kirk; Liu, Shenkui; Cui, Fuqiang (Frontiers in Microbiology, 2021)
Plant-beneficial microbes have drawn wide attention due to their potential application as bio-control agents and bio-fertilizers. Moso bamboo, which is among the monocots with the highest growth rate, lives perennially with abundant microbes that may benefit annually growing crops. Genome information of moso bamboo associated bacteria remains underexplored. We isolated and identified a novel Paraburkholderia strain Suichang626 from moso bamboo roots. Growth promoting effects of Suichang626 on both moso bamboo and seedlings of the model dicot Arabidopsis thaliana were documented in laboratory conditions. To gain insight into the genetic basis of this growth promotion effect, we sequenced the genome of Suichang626. Evidenced by genome-wide phylogeny data, we propose that Suichang626 is a novel strain of P. sacchari. Gene homologs encoding biosynthesis of the plant growth-promoting chemicals, acetoin and 2,3-butanediol, were identified in the genome of Suichang626. Comparative genomics was further performed with plant-beneficial and plant/animal pathogenic species of Paraburkholderia and Burkholderia. Genes related to volatile organic compounds, nitrogen fixation, and auxin biosynthesis were discovered specifically in the plant growth-promoting species of both genera.